Pancasila Accountability As A Criticism of Public Accountability Constructions In Indonesia - Rahmasari, Ratnida; Ludigdo, Unti; Djamhuri, Ali (Accounting Department,, 2024)
Purpose — This study aims to construct public accountability using the values ​​of Pancasila as a critique of the current practice of public accountability. Design/methodology/approach — This study uses Pancasila as a critical theory to critically examine current public accountability practices and to construct forms of Pancasila accountability. Findings — The results of this study indicate that an accountability crisis in public organization is due to the existing accountability construction has not accommodate Pancasila values. It leads to mismanagement of public organizations that are not incompatible with the constitution and the objectives of the state. This research also constructs Pancasila accountability as a critique of the existing construction of accountability. Pancasila accountability produces five forms of accountability, namely Divine, personal, and nationalistic accountability which emphasizes on personal/internal control from within (inward) of each individual, and political, managerial (hierarchial) accountability which emphasizes on external control mechanisms. Consistent with Pancasila, these five forms of accountability are interrelated and complement each other. Practical implications — This paper uses Pancasila value to construct public accountability in an effort to remind the readers and public of the important of bringing back Pancasila as basic value for achieving social justice and prosperity for the society in Indonesia. Originality/value — This paper uses Pancasila value as basic value to contruct public accountability. This construction is expected this will contribute to solving the accountability crisis in Indonesia. Keywords — Accoutability, Public Accountability, Pancasila, Inward Accountability, Ethic Paper type — Case study